PENGARUH MODAL KERJA DAN BIAYA OVERHEAD PABRIK TERHADAP LABA OPERASIONAL PADA PT. MEDCO ENERGI INTERNASIONAL Tbk. - Nur Afni, Febbyra (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
This study aims to determine the effect of working capital and factory overhead costs to operating profit at PT. Medco Energi International Tbk listed in Indonesia Stock Exchange. The variables used in this study is working capital, factory overhead costs and operating profit. The method used is descriptive method associative with a quantitative approach. The sample used is the quarterly financial statements. case study on PT. Medco Energi International Tbk, the period 2006-2013 and the sample in this study there are 32 samples. The analysis used is multiple linear regression, the classical assumption and hypothesis testing. Analysis was used to determine significant either partially or simultaneously. The test results showed that there was no significant effect between working capital to operating profit partially with thitung amounted to -1.042, while ttable is equal to 2.048, t count> t table (-1.042 <2.048) the hypothesis Ho is accepted HaExchange. The variables used in this study is working capital, factory overhead costs and operating profit. The method used is descriptive method associative with a quantitative approach. The sample used is the quarterly financial statements. case study on PT. Medco Energi International Tbk, the period 2006-2013 and the sample in this study there are 32 samples. The analysis used is multiple linear regression, the classical assumption and hypothesis testing. Analysis was used to determine significant either partially or simultaneously. The test results showed that there was no significant effect between working capital to operating profit partially with thitung amounted to -1.042, while ttable is equal to 2.048, t count> t table (-1.042 <2.048) the hypothesis Ho is accepted Ha rejected. Similarly, the factory overhead costs to significantly impact the operating profit amounted to 4.518 t-test, while ttable amounted to 2,048, according to the test criteria that if t count> t table (4.518> 2.048), the hypothesis H0 is rejected Ha accepted. Simultaneously working capital and factory overhead costs significantly affect the operating profit amounted to 10,862 while the value of F Ftable of 3.340, the F count> F (10,862> 3,340) then H0 is rejected.